Integration through comparative private law: Four lessons from Cappelletti - Infantino, Marta (International Journal of Constitutional Law, 2016)
The aim of this article is to explore Cappelletti’s most enduring teachings relevant to those who promote global or regional integration of private laws. The article will review Cappelletti’s insights into the dynamic history of law, the need to respect diversity and take into account society’s imbalances, and the duty of comparative lawyers to engage in “applied” interdisciplinary legal research.